The use of polyetherketoneketone in removable partial denture: Penggunaan polyetherketoneketone pada gigi tiruan sebagian lepasan - St. Rakhmawati A.; Rifaat Nurrahma; Eri Hendra Jubhari (Makassar Dental Journal PDGI Makassar, 2026)
Cobalt-chromium and titanium alloys are widely used as prosthetic frameworks due to their high strength, stiffness, corrosion iresistance, and passivation pro-perties. However, metal ions can potentially cause cytotoxicity, hypertension, and neoplasia. Polyetherketoneketone (PEKK) is an alternative polymer mate-rial that has physical, mechanical, and chemical properties suitable for use as denture framework material due to its high strength, low modulus of elasticity, and reduced risk of problems caused by metal frameworks such as allergies and potential me-tallic taste. In complex cases, the treatment plan and mate-rials used for the denture are important to ensure predictability and long-term du-rability. This review evaluates PEKK as a suitable biomaterial for removable partial denture frameworks. It is concluded that PEKK material is an alternative material that can be used as a removable partial denture framework because it is a lightweight framework material, has good biocompatibility, and is easy to repair in case of bone resorption.